Vocational education and training in Finland : short description - (:unkn) unknown (Publications Office of the European Union, 2019)
This short description contributes to better understanding of vocational education and training (VET) in Finland by providing insight into its main features and highlighting system developments and current challenges. It is published during the Finnish Presidency in the Council of the EU (second half of 2019). Finnish VET is highly regarded: 90% of Finns think it offers high-quality learning and 40% enrol in VET after basic education. The reasons include qualified and competent teaching, flexible qualifications, strong employment prospects and eligibility for further studies. VET flexibility is one of the Finnish system's greatest strengths. Personal development plans are created for each learner at the beginning of studies. Learners study only what they do not yet know; the more they know, the shorter their studies. The system is undergoing significant change. The 2018 reform is increasing the share of performance and effectiveness funding: these are to be based on the number of completed qualifications, on learners' access to employment or pursuit of further education, and on feedback from both learners and the labour market. (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; S 1.3 Berufliche Erstausbildung; S 1.5.2 Berufliche Weiterbildung; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungssteuerung; Bildungsfinanzierung; Bildungspersonal; Finnland